Bibliometric Analysis: Development of Community Based Tourism (CBT) - Based Educational Tourism in the Scopus Database (2014-2025) - Sugeng Handoko (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: This research aims to analyze the trends, intellectual structure and dynamics of the development of CBT-based educational tourism studies through a bibliometric analysis approach. Method: Data analysis was carried out using a bibliometric analysis approach by searching Use the "Insert Citation" button to add citations to this document. publications on the Scopus database for the 2014–2025 period using Harzing's Publish or Perish software. The data obtained was selected and cleaned, then analyzed descriptively to identify publication trends, source journals, and main authors. Next, keyword network mapping (co-occurrence) and author collaboration (co-authorship) was carried out using VOSviewer to reveal the thematic structure, dynamics of research development, and gaps in educational tourism studies based on Community Based Tourism (CBT). Result: The results of bibliometric analysis show that Community Based Tourism (CBT) educational tourism studies in the 2014–2025 period have experienced a significant increase, especially since 2019, with a peak in the number of publications in 2021. Citation analysis indicates the formation of core literature in the 2019–2022 period which has a high scientific impact, although publications in recent years have not shown large citations due to the time-lag effect. Keyword network mapping places community-based tourism as the main node that is strongly connected to the concepts of sustainability, sustainable development and community development, while educational tourism and rural tourism emerge as supporting themes that develop in an integrative manner. In addition, analysis of collaboration between countries shows a multipolar international network pattern with the dominance of the Asian region, especially Indonesia, as the center of research collaboration. Contribution: This study contributes by systematically mapping the development, intellectual structure, and thematic dynamics of educational tourism and Community-Based Tourism (CBT) research through a bibliometric approach based on Scopus data. The findings enrich the body of knowledge on sustainable tourism by affirming the role of educational tourism as a strategic instrument for strengthening community empowerment and fostering the development of rural tourism destinations. Furthermore, this study identifies research gaps in the areas of educational integration, community governance, and micro-level socio-economic impacts, which may serve as a foundation for future research agendas as well as for the formulation of policies and practices related to community-based educational tourism in Indonesia.